2005
DOI: 10.1007/s10856-005-2613-6
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine derived polycarbonate membrane is useful for guided bone regeneration in rabbit mandibular defects

Abstract: Standardized bilateral through-and-through defects (12x6 mm) were created extraorally in the mandibular angle of 18 New Zealand White rabbits. Animals were divided in to three groups (n=6) according to the intended healing time. On the left side, defects were covered with a poly(desaminotyrosyl-tyrosine-ethyl ester carbonate) (PDTE carbonate) membrane wrapped around the inferior border of the mandible and fixed with bioabsorbable sutures. On the right side, the defects were filled with a mesh made of bioactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…In cases where radiological ossification of the defect was complete, new bone formation was mainly seen at the outside of the membrane. The site treated with combination of membrane and BAG mesh seems to have healed more slowly, which is consistent with the radiological findings published earlier (Asikainen et al 2005).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In cases where radiological ossification of the defect was complete, new bone formation was mainly seen at the outside of the membrane. The site treated with combination of membrane and BAG mesh seems to have healed more slowly, which is consistent with the radiological findings published earlier (Asikainen et al 2005).…”
Section: Discussionsupporting
confidence: 91%
“…All sections were analysed by a single pathologist with a light microscope to record cellular reactions, membrane placement, new bone formation and localization. Samples obtained from the animals were radiographed as described earlier by the authors (Asikainen et al 2005). The radiographic results from weeks 12 to 24 have been described earlier (Asikainen et al 2005) and only 52 week samples are included in this study.…”
Section: Sample Preparation and Analysismentioning
confidence: 99%
“…19,20 Previous data have reported that poly(DTE carbonate) was biocompatible and osteoconductive in the distal femur and proximal tibia of rabbits, 21,22 a canine bone chamber model, 19 the calvaria of a rabbit non-CSD, 23 and rabbit mandibular defects. 24,25 However, despite the reported osteoconductive outcomes from those studies, bone regeneration was limited. These observations may have been caused by a mismatch between the poly(DTE carbonate) degradation to new bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…PDTEs have a variable pendant alkyl chain allowing for modulation of their thermal and mechanical properties with T g s of 50–81 °C, T m s of 75–118 °C, tensile strengths of 50–70 MPa and stiffnesses of 1–2 GPa 276. Their processibility has allowed for the fabrication of scaffolds composed of films,276–281 fibers,282 and gels 283, 284. PDTEs have been investigated for their potential in tissue engineering of bone,277, 278, 280 vasculature,283 and muscle 281.…”
Section: Hydrolytically Degradable Polymersmentioning
confidence: 99%
“…Their processibility has allowed for the fabrication of scaffolds composed of films,276–281 fibers,282 and gels 283, 284. PDTEs have been investigated for their potential in tissue engineering of bone,277, 278, 280 vasculature,283 and muscle 281. Slow degradation ( M w half life of over 200 days285) and minimal mass loss of PDTEs allows for them to maintain their physical properties for very long times making them good candidates for slow regenerative processes.…”
Section: Hydrolytically Degradable Polymersmentioning
confidence: 99%